ANALISIS KONDISI PERKERASAN JALAN PADA RUAS JALAN DESA MORELLA - Latukau, Hairani; Amaheka, Sammy G. M.; Wangean, Febrino (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
Roads are a vital transportation infrastructure that support all human activities. The increasing volume of vehicles each year has become one of the contributing factors to road damage in several regions of Indonesia. Infrastructure burdened by high and recurring traffic volumes will lead to a decline in road quality, both structurally and functionally. Observations were conducted on the road segment in Morella Village. The objective of this study is to determine an index value that can indicate the pavement condition and to identify the type of road treatment using the Pavement Condition Index (PCI) method. The study found the minimum index value on the Morella Village road segment was 67 at STA 0+300, which requires periodic improvement treatment, and the maximum index value was 100 at STA 0+200, requiring routine maintenance. Data analysis showed that the damage level on the Morella Village road segment from STA 0+000 to STA 2+000 is categorized as very good, with an average PCI value of 90.65, based on calculations of each 100-meter sample unit. Keywords: pavement condition index, treatment